Anthropometric and physiological characteristics of Melanesian futsal players: a first approach to talent identification in Oceania - Galy, Olivier; Zongo, Paul; Chamari, Karim; Michalak, Eric; Dellal, Alexandre; Castagna, Carlo; Hue, Olivier (Biology of Sport, 2015)
This study assessed the anthropometric and physiological characteristics of elite Melanesian futsal players in order to determine the best performance predictors. Physiological parameters of performance were measured in 14 Melanesian (MEL-G, 24.4±4.4 yrs) and 8 Caucasian (NMEL-G, 22.9±4.9) elite futsal players, using tests of jump-and-reach (CMJ), agility (T-Test), repeated sprint ability (RSA), RSA with change-of-direction (RSA-COD), sprints with 5 m, 10 m, 15 m, and 30 m lap times, and aerobic fitness with the 30-15 intermittent fitness test (30-15 IFT). The anthropometric data revealed significantly lower height for MEL-G compared with NMEL-G: 1.73±0.05 and 1.80±0.08 m, respectively; P=0.05. The CMJ was significantly higher for MEL-G than NMEL-G: 50.4±5.9 and 45.2±4.3 cm, respectively; P=0.05. T-Test times were significantly lower for MEL-G than NMEL-G: 10.47±0.58 and 11.01±0.64 seconds, respectively; P=0.05. MEL-G height was significantly related to CMJ (r=0.706, P=0.01), CMJ peakP (r=0.709, P=0.01) and T-Test (r=0.589, P=0.02). No significant between-group differences were observed for sprint tests or 30-15 IFT, including heart rate and estimated VO 2max . Between groups, the percentage decrement (%Dec) in RSA-COD was significantly lower in MEL-G than NMEL-G (P=0.05), although no significant difference was noted between RSA and RSA-COD. Within groups, no significant difference was observed between %Dec in RSA or RSA-COD; P=0.697. This study presents specific anthropometric (significantly lower height) and physiological (significantly greater agility) reference values in Melanesians, which, taken together, might help coaches and physical fitness trainers to optimize elite futsal training and talent identification in Oceania.